2016
DOI: 10.1007/978-3-319-22533-3_64
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intraspinal Pressure After Spinal Cord Injury: Technical Note from the Injured Spinal Cord Pressure Evaluation Study

Abstract: Intracranial pressure (ICP) is routinely measured in patients with severe traumatic brain injury (TBI). We describe a novel technique that allowed us to monitor intraspinal pressure (ISP) at the injury site in 14 patients who had severe acute traumatic spinal cord injury (TSCI), analogous to monitoring ICP after brain injury. A Codman probe was inserted subdurally to measure the pressure of the injured spinal cord compressed against the surrounding dura. Our key finding is that it is feasible and safe to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It is important to note that we monitor ISP from the subdural space, which is less invasive than intraparenchymal ISP. When the injured cord is swollen and compressed against the dura, subdural ISP equals intraparenchymal ISP at the injury site [ 13 , 17 , 26 ]. After a mild TSCI, the spinal cord may not be compressed against the dura; in this case, the relation between subdural versus intraparenchymal ISP is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that we monitor ISP from the subdural space, which is less invasive than intraparenchymal ISP. When the injured cord is swollen and compressed against the dura, subdural ISP equals intraparenchymal ISP at the injury site [ 13 , 17 , 26 ]. After a mild TSCI, the spinal cord may not be compressed against the dura; in this case, the relation between subdural versus intraparenchymal ISP is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that simultaneous monitoring of SCPP and microdialysis could be used to enhance drug entry at the injury site. Based on our current findings and earlier studies [4][5][6][7][8][9]20,21 , a large-scale study of outcome from TSCI in patients who have monitoring vs. those who do not is warranted.…”
Section: Annals Of Neurologymentioning
confidence: 61%
“…When the spinal cord is swollen and compressed against the dura, the subdural pressure (i.e., ISP) and intraparenchymal pressure at the injury site are the same. In this case, ISP is higher than cerebrospinal fluid (CSF) pressure above or below the injury site—details are given elsewhere [5, 6, 13–15]. …”
Section: Methodsmentioning
confidence: 99%